INFLUENCE OFDIFFERENTCONCENTRATION OF CURCUMIN (DIFERUOYL METHANE) ON FROZEN SEMEN QUALITY OF HOLSTEIN BULLS BORN IN IRAQ - Saleem, Abdul-Redha Hussein; Badry, Kareem Iwaid Al-; Ibrahim, FarisFaisel; J.Y, Khitam (International Journal of Psychosocial Rehabilitation, 2020)
Object :The current study was designed to improve semen preserve ability through the use of curcumin (diferuoyl methane) in different concentrations T1 0.5 ,T2 1.0 , T3 1.5 mM/ml and control (without additive) as extender additive expressed in frozen bull semen . Methods: Ejaculates less than 40% of initial individual motility were taken weekly from (3) Holstein bulls born in Iraq by using the artificial vagina. The semen samples were diluted with Tris containing different concentrations of curcumin (0.5, 1.0, 1.5)mM/ml and control (without additive), cooled slowly up to 5 Cº and equilibrated for 4hrs, semen was packed into 0.25 ml of straws and freezing and storage 48hrs in liquid nitrogen. Evaluated of semen for individual motility%, dead% ,abnormality%, acrosome integrity% and HOST%.at steps of freezing (after cooling and Post thawing). Results: Clearly indicated that, addition 1.5 mM of curcumin to tris diluents had significantly (P<0.05) higher individual motility%, acrosome integrity% and HOST Test% and less (P<0.05) sperm dead%, abnormality %in comparison to the 0.5 Mm of curcumin and control group. Besides, the addition of 1.0 mM of curcumin has also a promising effect when added to the tris-base diluents, while the addition of 0.5 mM of curcumin had their little or no effect on all properties which studies of cooled dilution semen and frozen in liquid nitrogen.in addition to present study revealed that Post-thawing had a clear effect, as it led to a significant (P<0.05) decrease in the individual motility%,acrosoma integrity % and HOS Test% of sperm also on other hand caused increased in Dead sperms%, abnormality sperms% compared with after cooling ,but addition curcumin in concentration1.5 mM/ml caused decrease this effect of freezing in some sperms properties such as individual motility% and abnormality% of sperms. Conclusion: Addition curcumin with concentration 1.5mM/ml To Tris diluent caused improve poor sperms properties of bulls and decrease effect of freezing on these samples.